Electro-oxidation of pyrene on glassy carbon electrode modified with fMWCNTs/CuO nanocomposite - Funmilola A Adesanya; Omolola E Fayemi (Materials Research Express, 2024)
The electrochemical oxidation of pyrene, a well-known polycyclic aromatic hydrocarbon, was investigated using a glassy carbon electrode (GCE) modified with nanocomposite of copper oxide nanoparticles incorporated functionalized multi-walled carbon nanotubes (fMWCNTs). The catalytic copper oxide nanoparticles (CuONPs) synthesized through a chemical co-precipitation method was combined with the highly electrically conductive functionalized multi-walled carbon nanotubes using a simple and efficient method. Several analytical techniques were employed in characterizing the nanomaterials namely: the scanning electron microscopy (SEM), energy-dispersive x-ray spectroscopy (EDS), transmission electron microscopy (TEM), Fourier-transform infrared (FTIR) spectroscopy, x-ray diffraction (XRD), and the ultraviolet–visible (UV–vis) spectroscopy, to validate the authenticity of the synthesis. The electrochemical behaviour of the proposed electrode was investigated in 10 mM [Fe(CN) _6 ] ^3-/4- via electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV), revealing the highest current response and lowest charge transfer resistance at the hybrid nanocomposite modified electrode (GCE/fMWCNTs/CuO NPs) in comparison with the other electrodes studied in this work (GCE, GCE/CuO NPs, and GCE/fMWCNTs. The electrocatalytic efficacy of the electrodes towards pyrene oxidation was also evaluated, with a similarly outstanding increment in the oxidation peak current response and highly reduced resistance to charge transfer at the nanocomposite-modified glassy carbon electrode. This enhanced electrocatalytic activity facilitated the transport of electrons between the pyrene molecules and the nanocomposite-modified electrode which is attributable to the synergy between the functionalized multi-walled carbon nanotubes and the copper oxide nanoparticles. The low detection limit of 1.30 μ M within the linear range (1.2–23.1 μ M) demonstrated by the sensor indicates its high sensitivity and potential for environmental based analytical applications such as pyrene detection.